Uji Sitotoksisitas dan Proliferasi Senyawa 1-(4-nitrobenzoiloksi- metil)-5-fluorourasil terhadap Sel Kanker Payudara MCF-7 (Cytotoxicity and Proliferation Studies of 1-(4-nitrobenzoyloxy- methyl)-5-fluorouracil) on Breast Cancer Cells MCF-7) - Eka Mustika Wati; Ayik Rosita Puspaningtyas; Dian Agung Pangaribowo (Pustaka Kesehatan, 2016)
1-(4-nitrobenzoyloxymethyl)-5-fluorouracil (4-NFU) is a derivative of anticancer drug 5-fluorouracil (5-FU) which has been substituted by alkyl, ester, benzene, and nitro groups at N1 position. 4-NFU has been synthesized by Kurnia but anticancer study has not been reported. This research aims to compare the cytotoxicity and antiproliferative activity between 4-NFU and 5-FU on MCF-7 cells. The cytotoxicity and antiproliferative activity were studied by MTT method. The cytotoxicity study was done for 24 hours. The antiproliferative study was done for 24, 48, and 72 hours. The result showed that cytotoxicity activity of 4-NFU (IC50 = 134.039 μM) was higher than 5-FU (IC50 = 4211.508 μM) on MCF-7 cells. Based on the unpaired t test, there was a significant difference between IC50 of 4-NFU and 5-FU (α<0.05). The antiproliferative study showed that there was a growth inhibition on MCF-7 cells. The doubling time value of 4-NFU was 290.51 hours at ½ IC50; 350.97 hours at IC50; and 418.2 hours at 1½ IC50. The doubling time value of 5-FU was 185.99 hours at ½ IC50; 214 hours at IC50; and 220.63 hours at 1½ IC50. The doubling time value of 4-NFU was higher than 5-FU so that antiproliferative activity of 4-NFU was higher than 5-FU on MCF-7 cells. Keywords: 1-(4-nitrobenzoyloxymethyl)-5-fluorouracil, cytotoxicity, proliferation, MCF-7